A Conversion to Civil Society? The Incomplete Reconfiguration of the Hizbullah Movement in Turkey. Issue 6 (1st November 2020) - Kurt, Mehmet
ABSTRACT: This article examines the incomplete transformation of the Kurdish Hizbullah from an illegal underground organization to a social and political movement influent in the Kurdish Turkey. The article contextualizes Hizbullah's transformation within the broader social and political developments after the 2000s. After a critical evaluation of the reconfiguration of the Kurdish political sphere in Turkey, the article critically addresses the Hizbullah's conversion to civil society. It analyses the Hizbullah's strategies of reorganization and mobilization through associations, political activism and public celebrations under the AKP rule. While acknowledging the political and social impact of this reconfiguration, this article also underlines the limits of this process, with a special focus on the Kurdish question and the ambivalent approach to Kurdish identity and martyrdom promoted by the political leaders and supporters of the movement. Relying on boundary making theory, the article argues that the Hizbullah's attempt to rearticulate religion and ethnicity to broaden its political and social base remains circumscribed by the hegemonic aspirations of the Turkish state on the one hand, and the ongoing antagonism with the Kurdish national movement on the other.